Bending capacity of corroded welded hollow spherical joints with considering interaction of tension force and bending moment. (December 2021) - Zhao, Zhongwei; Dai, Bozhi; Xu, Hao; Li, Tianhe
Abstract: Welded hollow spherical joints (WHSJs) are commonly used joints in reticulated shell structures. The WHSJs in actual projects are always subjected to tension force and moment. The appearance of tension force (TF) may affect the probability distribution of moment capacity for WHSJs with random corrosion. The stochastic FE analyses are conducted in this study to investigate the influence of TF on the probabilistic distribution of bending capacity of WHSJs. This study aims to investigate the influence of TF on bending capacity and construct a probabilistic distribution model of bending capacity considering the influence of TF. The proposed method for predicting probability distribution of reduction factor is also validated. Results show that the method has high accuracy in predicting the probabilistic distribution of bending capacity of WHSJs in complex force state. In addition, the proposed method is convenient for actual applications.